What Determines Electrochemical Surface Processes on Carbon Supported PdAu Nanoparticles? - Gallo, Ira B. C. [UNESP]; Carbonio, Emilia A.; Villullas, Hebe M. [UNESP] (Amer Chemical Soc, 2018)
Supported bimetallic nanoparticles have good activities in heterogeneous catalysis and electrocatalysts. Among those systems, PdAu shows improved stability and enhanced catalytic activity toward electrochemical reactions such as oxygen reduction, formic acid oxidation, and hydrogen evolution. The aim of this work was to study comprehensively the influence of ligand and ensemble effects on surface processes, such as oxide formation/reduction, oxidation of adsorbed CO, and adsorption of hydrogen, taking place on carbon-supported PdAu nanoparticles of different compositions. Toward that end, we thoroughly characterized the properties of PdAu/C catalysts with nominal Au contents of 20-50 atom % prepared by the same procedure and having similar average particle diameters. The combination of results obtained by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) indicates that nanoparticles had Pd-enriched surfaces and a Au-rich interior. X-ray absorption spectroscopy ()CAS) measurements around the Pd L3 edge evidenced that Au promotes an increase in the electronic occupation of the Pd 4d band, consistent with XPS results showing varying amounts of surfacelike and bulklike Pd oxide and metallic Pd. We show herein that ligand effects determine the formation of a Pd oxide layer on PdAu/C catalysts and ensemble effects govern hydrogen and CO adsorption. CO oxidation is delayed as the Au content increases as result of the decreasing availability of oxygen-containing species.
Keywords: bimetallic nanoparticles; ligand effects; ensemble effects; oxide formation/reduction; CO oxidation; hydrogen adsorption